A Dialogic Communication Perspective on Multi-stakeholder Collaboration: A Participatory Framework for Sustainable CSR - Darmawan, Ibnu; Mustofa, Ikrom (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2025)
Achieving effective Corporate Social Responsibility (CSR) requires a shift from passive assistance to participatory community development. This study analyzes how this principle led to the sustainable implementation of the Climate Village Program (Proklim) in Banguntapan. This project was realized through a multi-stakeholder collaboration involving PT AAF, GCI, and PUSPIK UII. The research specifically examines the role of the Participatory Rural Appraisal (PRA) model in ensuring local relevance. Using a qualitative, single case study design, the research applies Arnstein’s Ladder to measure involvement levels. Crucially, it also utilizes the Dialogic Ladder to assess the quality of two-way communication. Primary data was gathered via Focus Group Discussions (FGDs) and in-depth interviews centered on decision-making processes. Findings indicate that PRA successfully identified an urgent, community-driven need: the mentoring of ten sub-villages for Proklim implementation. The partners responded by pivoting the program's focus to support this local priority. This shift confirmed the achievement of the highest communication standard “authentic dialogue” defined by high mutuality and shared power. Ultimately, this outcome demonstrates that sustainable CSR relies on multi-stakeholder collaboration that empowers the community as the primary subject of development, reaching the level of